(3JYOjd GdeYjGQ aj fbO JfRjd GdCacGQs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3GKjQ GdOjf GdGHgQj , GdeaVd Hf YeQ Hf GdeaVd GdGHgQj GdSeQbfOj,J (B663 (3g` s
(3ChdgG (B:s
(3bGd ehdGfG eMeO Hf eMeO Hf GdMSf GdWhSi s
(3BNQgG (B:s
(3hHYO Cf YQV UGMH GdcJGH ai JCdja gPg GdebGdGJ GdYTQI s
(3Vef eLehY s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GSJOQGcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B279 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B315s
Keywords: (3GdadSaI hGdefWbs